Study on Ｒefining of Mg-6Al Alloy by Mg-7Sm-4Al Ｒefiner - GUO Er-jun; ZHANG Zhi; FENG Yi-cheng; WANG Li-ping (Journal of Harbin University of Science and Technology)
The Mg-7Sm-4Al refiner was prepared by adding Al and Sm elements to pure Mg，and the refiningeffect of the refiner on Mg-6Al alloy was studied. The comparative experiment was designed to directly add the same amount of Al and Sm. The effects of these two addition methods on the grain size of Mg-6Al alloy were discussed. The results showed that the addition of the Mg-7Sm-4Al refiner can refine the Mg-6Al alloy very well. When the addition amount of the Mg-7Sm-4Al was 36. 4% ，the average grain size of the Mg-6Al alloy was refined from the original 126. 12 μm to 75. 68 μm. The refiner mechanism was that the undissolved Al2 Sm particles in the Mg-7Sm- 4Al alloy act as a heterogeneous nucleation，soluble Al and Sm elements cause solute effects，and the two reasons together make the alloy refine. From the comparative experiment results of directly adding Al and Sm，it can be concluded that adding 0. 64% Sm could coarsen the grain of Mg-6Al alloy，due to Sm element removed oxide impurities，and took away the oxygen-rich heterogeneous in Mg-Al alloy，thus reducing the nucleation rate. When the addition amount of Sm reaches 2. 55% ，the alloy is refined，because Sm and Al formed Al2 Sm particles with heterogeneous nucleation ability.